Investigating Overlapping Genetic Factors and Novel Causal Genes in Autoimmune Diseases: A Transcriptome-Wide Association and Multiomics Study - Leihua Fu; Jieni Yu; Xin Wang; Zhe Chen; Jiaying Sun; Feidan Gao; Zhijian Zhang; Jiaping Fu; Pan Hong; Weiying Feng (International Journal of Genomics)
Conclusion: This study uncovers shared genetic factors across five autoimmune diseases, with FLOT1 identified as a novel causal risk gene for SLE. These findings suggest that platelet-mediated pathogenic mechanisms may contribute to SLE, providing a potential target for future therapeutic interventions.